Pengembangan Video Pembelajaran Biologi pada Materi Pokok Sistem Peredaran Darah untuk Siswa Kelas VIII SMP/MTs Tahun Ajaran 2021/2022 - Firda Yani; Laili Rahmi (Journal on Education, 2023)
This study aims to develop a learning video media on the subject matter of the human circulatory system for class VIII junior high school students. The form of this research is research and development or research and development using the Four-D (4D) model by Thiagarajan (1974). This media development research was carried out from the define, design, and development stages. The sampling technique used by the researcher is a purposive sampling technique with 10 students from three different schools; SMPN 2 Ukui, SMPN 3 Ukui, and SMPN 5 Ukui. In the data collection technique carried out, it was obtained from the results of validation by validators of learning media experts, material experts, and class VIII Biology teachers. The data analysis technique used is descriptive analysis. The results of this study are kinemaster products on the human respiratory system material in the form of video (mp4). The results of validation by learning media experts indicate that the developed learning media is very feasible to use with an average percentage of 90.06%. The results of the validation of the material experts indicate that the learning media developed by the researcher is very feasible to use with an average percentage of 90%. And the results of validation by three Biology teachers who teach in each school show that the developed learning media is very feasible to use with an average percentage of 95.05%. The learning media developed by students is very feasible with an average percentage of 95.99%. developed by students is very feasible with an average percentage of 96.91%. Based on the validation results from the experts, it was obtained that the video media product for learning biology on the subject matter of the human circulatory system is very suitable to be used as a medium for learning Biology..